2021
DOI: 10.3389/fimmu.2021.719544
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Is a Potential Biomarker to Discriminate Active Adult-Onset Still’s Disease From COVID-19

Abstract: BackgroundHyperinflammation with dysregulated production of galectins and cytokines may develop in COVID-19 or adult-onset Still’s disease (AOSD). Given the similar clinical features in both diseases, it is necessary to identify biomarkers that can differentiate COVID-19 from AOSD. However, the related data remain scarce currently.MethodsIn this cross-sectional study, plasma levels of galectin-3, galectin-9, and soluble TIM-3 (sTIM-3) were determined by ELISA in 55 COVID-19 patients (31 non-severe and 24 sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…A Turkish study extended these findings by showing that galectin-3 levels were significantly increased among patients with severe COVID-19 compared to non-severe cases and that galectin-3 levels were higher in patients with COVID-19 compared to healthy controls (median of severe COVID-19, 415.31 pg/mL; IQR, 122.81-1622.23 vs. median of non-severe, 326.33 pg/mL; IQR, 100.09-1271.04 vs. median of healthy controls 243.13 pg/mL, 166.57-380.41) [101]. Higher levels of galectin-3 among COVID-19 patients were also reported in a rather small Taiwanese study [102].…”
Section: Galectin-3supporting
confidence: 51%
“…A Turkish study extended these findings by showing that galectin-3 levels were significantly increased among patients with severe COVID-19 compared to non-severe cases and that galectin-3 levels were higher in patients with COVID-19 compared to healthy controls (median of severe COVID-19, 415.31 pg/mL; IQR, 122.81-1622.23 vs. median of non-severe, 326.33 pg/mL; IQR, 100.09-1271.04 vs. median of healthy controls 243.13 pg/mL, 166.57-380.41) [101]. Higher levels of galectin-3 among COVID-19 patients were also reported in a rather small Taiwanese study [102].…”
Section: Galectin-3supporting
confidence: 51%
“…These studies also showed that the serum IL-18 levels in patients with sepsis were approximately 100 pg/mL, which is significantly lower than the levels in AOSD patients. Interestingly, Chen et al recently reported that serum IL-18 levels at the cut-off value 190.5 pg/ml had high discriminative ability for AOSD and coronavirus disease 2019 (COVID-19), with ROC-AUC 0.948, sensitivity 91.3% and specificity 95.8% (34).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that Gal-3 levels in macrophages, monocytes, and dendritic cells were increased in patients with severe COVID-19, compared with mild diseases ( Figure 1 ) ( 127 ). Moreover, the serum level of Gal-3 was significantly higher in severe COVID-19 patients, compared with healthy controls ( 69 , 128 ). It has been reported that Gal-3 was upregulated in proliferating T cells in severe cases of COVID-19, and frequently the hyperinflammation phase involves the overexpression of Gal-3, TNF-α, and IL-6 ( 129 ).…”
Section: Immune Checkpoint Ligands In Covid-19mentioning
confidence: 84%
“…Another study observed significant elevations of soluble TIM-3 (sTIM-3) and soluble LAG-3 (sLAG-3) in severe COVID-19 patients, compared with mild disease ( 44 ). Furthermore, Chen et al found that the plasma level of sTIM-3 was significantly higher in severe COVID-19 patients, compared with healthy controls ( 69 ). Moreover, Diao et al showed a significant increase in TIM-3 expression on peripheral blood CD4+ T cells in COVID-19 patients, which could contribute to the functional exhaustion of these cells ( 67 ).…”
Section: Inhibitory Immune Checkpoints In Covid-19mentioning
confidence: 99%